2010
DOI: 10.1177/0271121410369708
|View full text |Cite
|
Sign up to set email alerts
|

Using a Constant Time Delay Procedure to Teach Foundational Swimming Skills to Children With Autism

Abstract: The purpose of this study was to evaluate the effectiveness of using a constant time delay procedure to teach foundational swimming skills to three children with autism. The skills included flutter kick, front-crawl arm strokes, and head turns to the side. A multiple-probe design across behaviors and replicated across participants was used. Results of the study indicated that the constant time delay procedure was effective in teaching foundational swimming skills to the three children. Implications for future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 8 publications
3
44
0
2
Order By: Relevance
“…Este resultado difiere de la observada por Chu y Pan (18) , Pan (20) y Rogers, Hemmeter y Wolery (23) . Estos autores encontraron que los estudiantes demostraron facilidad o que ya realizaban entradas en la piscina de modo independiente o con ayuda mínima, y por lo tanto, con un mejor desempeño en las tareas relacionadas con la natación.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Este resultado difiere de la observada por Chu y Pan (18) , Pan (20) y Rogers, Hemmeter y Wolery (23) . Estos autores encontraron que los estudiantes demostraron facilidad o que ya realizaban entradas en la piscina de modo independiente o con ayuda mínima, y por lo tanto, con un mejor desempeño en las tareas relacionadas con la natación.…”
Section: Discussionunclassified
“…Rogers, Hemmeter y Wolery (23) informaron que los estudiantes tardaron entre 6-8 sesiones para adquirir una nueva habilidad entre las tres estudiadas: pierna crol, brazada de crol y la respiración lateral. Al final de 15 sesiones, en este estudio, todos los participantes mostraron mejorías en tareas evaluadas para las entradas y salidas, pero para el resto de los estudiantes, las habilidades se han desarrollado de manera diferente entre uno y otro.…”
Section: Discussionunclassified
“…Three of these studies tried to examine the effectiveness of the "constant time delay" procedures on simple aquatic skills of children with ASD and Pervasive developmental disorder not otherwise specified (Rogers et al, 2010;Yilmaz et al, 2005;Yilmaz, Konukman, Birkan, Ozen, et al, 2010).…”
Section: Intervention Programsmentioning
confidence: 99%
“…Five studies used the Halliwick Concept (Bumin, Uyanik, Yilmaz, Kayihan, & Topcu, 2003;Chu & Pan, 2012;Hillier, McIntyre, & Plummer, 2010;Yilmaz, Konukman, Birkan, Ozen, et al, 2010;Yilmaz, Yanardağ, Birkan, & Bumin, 2004) and three studies reported swimming as the main intervention (Casey, Rasmussen, Mackenzie, & Glenn, 2010;Oh, Licari, Lay, & Blanksby, 2011;Rogers, Hemmeter, & Wolery, 2010). Three studies implemented a combined program of exercises in water and swimming (Fragala-Pinkham, Haley, & O'Neil, 2011;Pan, 2010;Yilmaz et al, 2009), and in four studies exercises in water and games were the main content (Ennis, 2011;Pan, 2011;Yilmaz, Birkan, Konukman, & Erkan, 2005;Yilmaz, Konukman, Birkan, & Yanardag, 2010).…”
mentioning
confidence: 99%
“…Harrison & Pyles, 2013;Kladopoulos & McComas, 2001;Quinn, Miltenberger, & Fogel, 2015;Stokes, Luiselli, Reed, & Fleming, 2010), relatively fewer studies have focused on teaching sports-related recreation behaviors to individuals with disabilities. Furthermore, many of these studies focused on increasing physical activity through solitary activities such as swimming or participating in treadmill programs, often in relation to a goal of decreasing problematic behavior (e.g., stereotypy, off-task behaviors; see Celiberti, Bobo, Kelly, Harris, & Handleman, 1997;Nicholson, Kehle, Bray, & Van Heest, 2011;Rogers, Hemmeter, & Wolery, 2010). Thus, although common behavior-analytic approaches to addressing skill deficits (e.g., discrete trial training, response chaining, shaping, etc.)…”
mentioning
confidence: 99%